12-channel USB data acquisition system for QT dispersion analysis - J., M. Najeb; Ruhullah, Arief; Salleh, Sh-Hussain (2005)
QT dispersion has been generally agreed that it is a marker for the sudden cardiac death. Therefore an automated QTd analysis system is crucial in detecting the symptoms. Various systems have been developed in this field to support various medical and sports practice. The 12-lead electrocardiogram system is one of them. PC-base electrocardiogram system with automated analysis has been in the market for years. However these systems adapt the conventional parallel port and serial port PC interface. Various products have been developed based on the popular USB communication because of its capability to plug multiple USB devices via a USB hub and its unique identification of the type of device plugged in. The purpose of this paper is to describe the development of a 12-channel USB data acquisition system for electrocardiogram as part of an automated QTd analysis system. This paper however focuses only on the development of the digital side of the system. The data acquisition is interfaced to the PC via a USB module base on the FTDI Chip hassle free USB interface module. The 12-bit resolution data acquisition system based on PIC16F84A-20 has been able to sample at 500 Hz per channel for 12 channels and plotting is done on a simultaneous real-time basis.